2012
DOI: 10.4103/0970-9185.98337
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of propofol and thiopentone for electroconvulsive therapy

Abstract: Objectives:To compare propofol and thiopental as anesthetic agents for electroconvulsive therapy (ECT) with respect to seizure duration, stimulus charge, and clinical effects.Materials and Methods:Randomized, blinded study of 28 patients of depression treated with bilateral ECT. In group P (n = 14), sedation was achieved with propofol 1.5 mg/kg, whereas in group T (n = 14), it was achieved with thiopentone 3 mg/ kg IV. Succinylcholine 0.4 mg/kg intravenous was given in all patients as for neuromuscular blockad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 16 publications
(22 reference statements)
4
32
2
Order By: Relevance
“…Complications can thus be related to thiopental here. Indeed, during a study in which thiopental and propofol were compared, propofol was found to be more reliable in terms of hemodynamic parameters (Kumar et al 2012). And when complications were examined in this particular case, there was greater allergic reaction against the anesthetic agent used in Clinic-II.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Complications can thus be related to thiopental here. Indeed, during a study in which thiopental and propofol were compared, propofol was found to be more reliable in terms of hemodynamic parameters (Kumar et al 2012). And when complications were examined in this particular case, there was greater allergic reaction against the anesthetic agent used in Clinic-II.…”
Section: Discussionmentioning
confidence: 91%
“…While there are publications which consider eff ective duration to be between the range of 15 -120 s and 25 s in general across the world (Kumar et al 2012), in previous studies performed in Turkey (Alg ü l et al 2009;Y ı ld ı z et al 2003) 20 s was accepted as the standard for suffi cient seizure duration in the Psychiatric Association of Turkey handbook (Tomruk et al 2007b) and 25 s for active seizure. During this study, it was observed that psychiatrists who have received diff erent training and worked independently from each other exhibit a common approach in applying ECT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] There have also been some studies and case reports reporting the low dose thiopental effects in adults. [27][28][29] These were usually about ambulatory and emergency interventions such as short operations, diagnostic and therapeutic procedures and transportation. In this present study, we preferred to use low dose thiopental for sedation because of avoiding either the hypotensive effects of propofol or the lower neonatal Apgar and neurobehavioral scores of both midazolam and propofol.…”
Section: Discussionmentioning
confidence: 99%
“…Of these 89 studies, 24 were RCTs (Abdallah, Fasula, Kelmendi, Sanacora, & Ostroff, 2012;Abdollahi et al, 2012;Bailine et al, 2010;Bjølseth et al, 2015;Brakemeier et al, 2014;Ghasemi et al, 2014;Hansen et al, 2011;Kayser et al, 2011;Kellner et al, 2010;Keshtkar, Ghanizadeh, & Firoozabadi, 2011;Kumar, Sharma, & Mani, 2012;Loo et al, 2012;Loo et al, 2015;Masoudzadeh, Yahyavi, Rashidi, Mohammadpour, & Kiani, 2013;Matthews et al, 2013;Mayur, Bray, Fernandes, Bythe, & Gilbett, 2010;Mayur, Byth, & Harris, 2013;Purtuloglu et al, 2013;Quante et al, 2011;Roepke et al, 2011;Spaans et al, 2013;Wang et al, 2012;Yildiz et al, 2010;Yoosefi et al, 2014); and five were non-randomized trials (Allen et al, 2015;Aten, Oudega, van Exel, Stek, & van Waarde, 2015;Gedge et al, 2012;Lin et al, 2014;Okamoto et al, 2010).…”
Section: Focus and Design Of The 91 Studiesmentioning
confidence: 99%